Perlindungan Hak Anak Dibawah Umur dalam Gugatan Warisan - Thurfah Bilqis Sa’iidah; Ria Anggraini; Muhamad Wildan Alfarezi; Rizha Claudilla Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
Protecting the rights of children in inheritance cases is very important in Indonesian civil law. It involves things like legal ability, who takes care of the child, and making sure the child's rights are properly respected and met. This study looks into how the law protects young people in fights over inheritance, including how guardians are used, any problems where someone might benefit unfairly, and how judges should make sure the child's best interests are always considered. The study uses a normative legal approach, looking at laws and ideas by checking related civil law rules and child protection guidelines. The study shows that children cannot make their own legal decisions in court and need their parents or guardians to act on their behalf. But in real situations, there can be problems where the parents' interests might conflict with what's best for the child, which could affect the child's right to inherit property. Judges are important in checking if the guardian has the right to be in the case and making sure the claim doesn't harm the child. Legal protection in inheritance matters needs to be both official, by having proper representatives, and real, by ensuring fair treatment, clear laws, and special care for children's rights as legal beings who need extra protection.